2018
DOI: 10.1021/acs.chemmater.8b01699
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effective Vertical Carbon Nanosheets/Iron-Based Composites as Efficient Electrocatalysts for Water Splitting Reaction

Abstract: Developing low-cost and highly active catalysts is vital to achieve efficient electrochemical water splitting for hydrogen production, which is considered as a very promising approach for renewable energy storage. Herein, an efficient and cost-effective electrode architecture constructed by vertically aligned carbon nanosheets (VCNs) and iron oxyhydroxide/nitride (VCNs@FeOOH//VCNs@Fe4N) is designed and synthesized for water splitting in alkaline medium. Benefiting from the highly exposed active sites, accelera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 64 publications
1
34
0
Order By: Relevance
“…[1] Specifically,constructing carbon-based hybrid nanomaterials has provided an opportunity to enable synergic effects between the individual components.Considerable progress has been achieved in the rational design of carbon hybrids towards energy-related electrochemical devices,for example,rechargeable metal-ion batteries,s upercapacitors,m etal-air batteries,a nd water splitting devices. [2] However, designing and tailoring the functional building blocks for hybrid structures with high reactivity,g ood electrical conductivity and excellent structural stability remains af ormidable challenge.R ecently, electrospinning has emerged as an effective technique allowing for the controlled formation of multichannel carbon-fiber networks with tunable porosity,assemblies and architectures. Furthermore,i ncorporation of active species into welldefined carbonaceous matrixes as freestanding electrodes gives desirable conductivity and flexibility,w hich is particularly appealing with regard to both electrochemical reactions and practical applications.…”
mentioning
confidence: 99%
“…[1] Specifically,constructing carbon-based hybrid nanomaterials has provided an opportunity to enable synergic effects between the individual components.Considerable progress has been achieved in the rational design of carbon hybrids towards energy-related electrochemical devices,for example,rechargeable metal-ion batteries,s upercapacitors,m etal-air batteries,a nd water splitting devices. [2] However, designing and tailoring the functional building blocks for hybrid structures with high reactivity,g ood electrical conductivity and excellent structural stability remains af ormidable challenge.R ecently, electrospinning has emerged as an effective technique allowing for the controlled formation of multichannel carbon-fiber networks with tunable porosity,assemblies and architectures. Furthermore,i ncorporation of active species into welldefined carbonaceous matrixes as freestanding electrodes gives desirable conductivity and flexibility,w hich is particularly appealing with regard to both electrochemical reactions and practical applications.…”
mentioning
confidence: 99%
“…Fe 2p spectra (Figure 4(b) and Figure S10) confirm the presence of Fe species as FeOOH [38,39], with the coexistence of Fe 2+ and Fe 3+ at 710.7/724.8 eV and 712.8/727.8 eV, respectively. The peak intensity for Fe 2p 1/2 , 2p 3/2 , and satellite together enlarged from V 2 O 5 @FeOOH-1 to V 2 O 5 @FeOOH-5, in accordance with the increasing incorporation of Fe species within the heterostructure (Table S1).…”
Section: Resultsmentioning
confidence: 74%
“…The heteroatoms of B, S, N, P, F, and O hold great potential to alter the intrinsic properties of graphene based materials and enable them to adsorb reactant species on their surface without disturbing their electrical conductivities, which shows the availability of foundation for unusual catalytic performances [65][66][67][68]. Furthermore, it has (4) [118] CoO/NC Pyrolysis 1.0 M KOH 1.55 [151] CoP/NC Annealing 1.0 M KOH 1.73 [147] CoP/rGO Annealing/phosphoration 1.0 M KOH 1.56 [138] CoP/rGO Pyrolysis 1.0 M KOH 0.47 [145] Co-BNC Carbonization 1.0 M KOH 1.68 [180] CoP/NPMG Carbonization 1.0 M KOH 1.60 [149] NiP/C Electrodeposition/phosphoration 1.0 M KOH 1.63 [146] VCN@Fe 4 N/FeOOH Annealing 0.1 M KOH 1.60 [153] NiFe-LDH NS@DG Suspension 1.0 M KOH 1.50 [156] been noted that the modification of graphene via high electronegative heteroatom (e.g., N, F, and O) doping can easily modulate the electronic structures by activating the adjacent carbon atoms in the graphene, leading to increase catalytic sites, which ultimately boosts up the electrochemical activities for water splitting [69]. In addition, the co-doping with higher and lower electronegative heteroatoms can also provide a synergistic effect between heteroatoms with a distinctive electronic structure and consequently enhance the activity of heteroatom-doped graphene-based electrocatalysts [70].…”
Section: Heteroatom-doped Graphene-based Electrocatalysts For Water Smentioning
confidence: 99%
“…Structural characterization indicated that the high catalytic activities of as-prepared CoO x @CN were linked to the synergistic effect between CoO and Co, promising conductivity of N-doped carbon, and the presence of electron rich N atoms. A bifunctional electrocatalyst based on iron oxyhydroxide/nitride (FeOOH/FeN 4 ) and vertically aligned carbon nanosheets (VCNs) was fabricated by a template method, followed by pyrolysis of VCNs and iron-based precursors at 500 °C to conduct overall water splitting [153]. Acting as an OER electrocatalyst, the VCNs@FeOOH displayed an overpotential of ~ 0.18 V at 10 mA cm −2 .…”
Section: D Carbon-based Hybrid Electrocatalysts For Overall Water Spmentioning
confidence: 99%